BENTUK PERTANGGUNGJAWABAN INDONESIA TERHADAP MALAYSIA DAN SINGAPURA DALAM MASALAH KABUT ASAP DI PROPINSI RIAU - Suadela Liu; Suhaidi Suhaidi; Jelly Leviza (Journal of USU International Law, 2013)
ABSTRACT Forest fires have become an international concern for environmental and economic issues. Smoke disruption  due to forest fire in Indonesia has crossed the states lines. Meanwhile, the provisions of International law for the state responsibility issue has not been established. The principle of state responsibility exists from the international primary rules of obligation, balance between rights and obligations of states. Each country that holds a certain rights also supports a particular obligations as well. This obligations is another side of the rights that been granted by law. That in practice application of this principle still unable to restore the environmental to its original state. This special nature immediately suggests that there is another needs for few more forms of application of the international law principles to ensure that the law is capable as the first instrumen of the environmental protection. Key words : Forest fires, International Law, Indonesia